Differential Growth Responses of Soil Bacterial Taxa to Carbon Substrates of Varying Chemical Recalcitrance - Goldfarb, Katherine C.; Karaoz, Ulas; Hanson, China A.; Santee, Clark A.; Bradford, Mark A.; Treseder, Kathleen K.; Wallenstein, Matthew D.; Brodie, Eoin L. (Frontiers in Microbiology, 2011)
Soils are immensely diverse microbial habitats with thousands of co-existing bacterial, archaeal and fungal species. Across broad spatial scales, factors such as pH and soil moisture appear to determine the diversity and structure of soil bacterial communities. Within any one site however, bacterial taxon diversity is high and factors maintaining this diversity are poorly resolved. Candidate factors include organic substrate availability and chemical recalcitrance, and given that they appear to structure bacterial communities at the phylum-level, we examine whether these factors might structure bacterial communities at finer levels of taxonomic resolution. Analyzing 16S rRNA gene composition of nucleotide analog-labeled DNA by PhyloChip microarrays, we compare relative growth rates on organic substrates of increasing chemical recalcitrance of >2,200 bacterial taxa across 43 divisions/phyla. Taxa that increase in relative abundance with labile organic substrates (i.e. glycine, sucrose) are numerous (>500), phylogenetically-clustered, and occur predominantly in two phyla (Proteobacteria and Actinobacteria) including orders Actinomycetales, Enterobacterales, Burkholderiales, Rhodocyclales, Alteromonadales and Pseudomonadales. Taxa increasing in relative abundance with more chemically recalcitrant substrates (i.e. cellulose, lignin or tannin-protein) are fewer (168) but more phylogenetically-dispersed, occurring across 8 phyla and including Clostridiales, Sphingomonadalaes, Desulfovibrionales. Just over 6% of detected taxa, including many Burkholderiales increase in relative abundance with both labile and chemically recalcitrant substrates. Estimates of median rRNA copy number per genome of responding taxa demonstrate that these patterns are broadly consistent with bacterial growth strategies. Taken together, these data suggest that changes in availability of intrinsically labile substrates may result in predictable shifts in soil bacterial composition.